Tunisia : Statistical Annex. (IMF Staff Country Reports; Country Report, 1995)
This paper summarizes the economic progress achieved by Tunisia during the first half of the 1990s. The paper highlights the main changes including the adoption of a new banking law, the introduction of an interbank foreign exchange market, the issuance of negotiable treasury bills, and the revision of the stock market law. The paper discusses the new banking law, passed in February 1994, to strengthen banks' role in the economy. The law introduces 'universal banking' and permits deposit money banks to expand their activities to new areas.